1999
DOI: 10.1177/004728759903800207
|View full text |Cite
|
Sign up to set email alerts
|

U.S. International Pleasure Travelers’ Images of Four Mediterranean Destinations: A Comparison of Visitors and Nonvisitors

Abstract: This study compares U.S. international pleasure travelers’ images of four Mediterranean destinations—Turkey, Egypt, Greece, and Italy—for both visitors and nonvisitors. The image construct was conceptualized as having three components: cognitive, affective, and overall image. MANOVA analysis indicated that significant differences exist in all image components between the four destination countries. The findings revealed strengths and weaknesses of the four competing destinations and implications for positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
280
3
36

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(332 citation statements)
references
References 30 publications
9
280
3
36
Order By: Relevance
“…Numerous researchers have argued that the holistic representation of images is greater than the sum of its components (Fakeye & Crompton, 1991;Phelps, 1986). Researchers who have emphasized the role of cognitive and affective destination images include some who have conceptualized holistic image as a third component of destination perceptions, which involves the global impressions of tourists, and which supplements cognitive and affective perceptions or is a subset of them (Baloglu & Love, 2005;Baloglu & McCleary, 1999b). Again, there are conflicting views of the relationships among cognitive, affective, and holistic images.…”
Section: Intention To Revisit a Destinationmentioning
confidence: 99%
“…Numerous researchers have argued that the holistic representation of images is greater than the sum of its components (Fakeye & Crompton, 1991;Phelps, 1986). Researchers who have emphasized the role of cognitive and affective destination images include some who have conceptualized holistic image as a third component of destination perceptions, which involves the global impressions of tourists, and which supplements cognitive and affective perceptions or is a subset of them (Baloglu & Love, 2005;Baloglu & McCleary, 1999b). Again, there are conflicting views of the relationships among cognitive, affective, and holistic images.…”
Section: Intention To Revisit a Destinationmentioning
confidence: 99%
“…The discussion and interviews with experts had an aim to increase the content validity of the scale and to supplement or change attributes -questions in the questionnaire. Based on qualitative research, it has been concluded that the term "Malaysian food" should be changed to "Local food", since previous studies (Baloglu, McCleary, 1999) have shown that the notion of "local food" contributes to the popularity of a tourist destination and consumption of food. In a research conducted in four Mediterranean countries, Italy has achieved the greatest success using the term "local food" or local cuisine (Baloglu, McCleary, 1999).…”
Section: Instrumentmentioning
confidence: 99%
“…The complexity of identifying a single destination, however, is complicated by the fact that a destination may include several towns, cities or municipalities, other government provinces or even an island archipelago may be the entire country; place branding, travel, tourism and brand management literature provide ample evidence of the forgoing Bramwell and Rawding, 1996 ;Wilson et al ., 2001 ;O ' Leary and Deegan, 2005 ;Baloglu and McCleary, 1999 ;Kerr, 2006 ). Decorously, the form of geographical entity does not limit the scope of destination branding provided a direct association with tourism is established, although it has been noted that destination branding has been confl ated with nation branding ( Anholt, 2005 ).…”
Section: ' Place ' and Associated Vocabularymentioning
confidence: 99%